Characterisation and development of histopathological lesions in a guinea pig model of Mycobacterium tuberculosis infection - Larenas-Muñoz, Fernanda; Ruedas-Torres, Inés; Hunter, Laura; Bird, Alison; Agulló-Ros, Irene; Winsbury, Rebecca; Clark, Simon; Rayner, Emma; Salguero, Francisco J. (Frontiers in Veterinary Science, 2023)
Tuberculosis (TB) remains a very significant infectious disease worldwide. New vaccines and therapies are needed, even more crucially with the increase of multi-drug resistant Mycobacterium tuberculosis strains. Preclinical animal models are very valuable for the development of these new disease control strategies. Guinea pigs are one of the best models of TB, sharing many features with the pathology observed in human TB. Here we describe the development of TB lesions in a guinea pig model of infection. We characterise the granulomatous lesions in four developmental stages (I-IV), using histopathological analysis and immunohistochemical (IHC) techniques to study macrophages, T cells, B cells and granulocytes. The granulomas in the guinea pigs start as aggregations of macrophages and few heterophils, evolving to larger lesions showing central caseous necrosis with mineralisation and abundant acid-fast bacilli, surrounded by a rim of macrophages and lymphocytes in the outer layers of the granuloma. Multinucleated giant cells are very rare and fibrotic capsules are not formed in this animal model. Department of Health and Human Services, under Contract No. 75N93021C00029. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.